Quality Assessment of Colonoscopies Performed by Resident Physicians in Colorectal Surgery - Giongo, Sofia Marasca; Fillmann, Henrique Sarubbi; Fillmann, Lucio Sarubbi; Padoin, Alexandre Vontobel (Journal of Coloproctology, 2024)
Introduction Colorectal cancer is the third most common malignant neoplasm worldwide, with ∼ 150 thousand new cases each year. Screening policies have brought significant progress due to the possibility of early diagnosis and polyp resection. Therefore, there is a need for continuous evaluation of the quality of colonoscopies based on well-established criteria in the literature.Materials and Methods The present retrospective study assesses the quality of colonoscopies performed at a tertiary hospital, comparing resident physicians with their preceptors. A total of 422 preceptor exams and 115 resident exams were evaluated, with a comparison of the adenoma detection rate, cecal intubation rate, examination time, and bowel preparation quality.Results The adenoma detection rate in the exams performed by preceptors was of 46.9%, while in those performed by residents, it was of 35.2% (p = 0.038). The cecal intubation rate was of 98.6% in the preceptor group and of 94.8% in the resident group (p = 0.025). The median total examination time was of 13 minutes and 42 seconds in the preceptor group and of 19 minutes and 22 seconds in the resident group (p < 0.005).Conclusion During their training, resident physicians perform an adequate number of colonoscopies, which enables them to achieve adenoma detection rates, cecal intubation and examination times within the limits proposed by the literature.
Keywords: colorectal neoplasia; colonic polyps; endoscopy